2017
DOI: 10.18485/esptoday.2017.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

English for Business: Student Responses to Language Learning Through Social Networking Tools

Abstract: This action research based case study addresses the situation of a first year class of Business English students at Universidad de Alcalá and their attitudes towards using Web 2.0 tools and social media for language learning. During the semester, the students were asked to collaborate in the creation and use of some tools such as blogs, video repositories (YouTube), networking programs (LinkedIn), and communication tools (SlideShare). The data were obtained through an online questionnaire designed after a focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In addition, studies of ESBP in particular have shown that being effective in CMC is now one of the most important skills that business people need (Gimenez, 2014;Lockwood, 2017). This research suggests that for learners of business English in particular, flipping the classroom and simultaneously introducing CMC into the curriculum through the use of ICT, may not only provide learners with a motivating and effective way of learning (Laborda & Litzler, 2017;Rapanta et al, 2014), it may also provide them with an opportunity to develop a set of crucial communication skills. As Zhang (2007Zhang ( , 2016 has suggested, focused language practise like this makes an important contribution to business English teaching as it allows students to combine their language skills and their knowledge of the business world.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, studies of ESBP in particular have shown that being effective in CMC is now one of the most important skills that business people need (Gimenez, 2014;Lockwood, 2017). This research suggests that for learners of business English in particular, flipping the classroom and simultaneously introducing CMC into the curriculum through the use of ICT, may not only provide learners with a motivating and effective way of learning (Laborda & Litzler, 2017;Rapanta et al, 2014), it may also provide them with an opportunity to develop a set of crucial communication skills. As Zhang (2007Zhang ( , 2016 has suggested, focused language practise like this makes an important contribution to business English teaching as it allows students to combine their language skills and their knowledge of the business world.…”
Section: Introductionmentioning
confidence: 93%
“…Working with on-line materials and allowing mobile learning to replace conventional learning can be very seductive, as the majority of students enjoy the freedom it allows and their motivation tends to remain high (Laborda & Litzler 2017;Nicholas et al, 2010;Rapanta et al, 2014). While research also suggests that learning outcomes can be influenced positively through the introduction of mobile learning, (e.g.…”
Section: Structuring Mobile Learning: Interaction Production and Refmentioning
confidence: 99%
See 1 more Smart Citation
“…These skills are expected not only to enable students to organize knowledge, but also to improve their public speaking skills. Because skills such as presenting ideas in a systematic way and speaking effectively to an audience are necessary for university graduates (Artyushina, Sheypak, & Khovrin, 2010;García-Laborda & Litzler, 2017), oral presentation has been the main focus of various courses at the university level.…”
Section: Introductionmentioning
confidence: 99%
“…(P6) Employing various learning platforms to support distance learning was also reported in a study by Atmojo & Nugroho (2020). Using not only a single learning platform to support ESP materials and tasks concurs is beneficial (Laborda & Litzler, 2017). The decision to make use of more than one learning platform could mean that no single digital learning medium is perfect.…”
Section: Using Various Learning Platformsmentioning
confidence: 92%